Optimization of structural and mechanical systems - Arora, Jasbir S. (World Scientific, 2007)
This book provides a discussion of the general impact of WTO membership on both sides of the Taiwan Strait, and addresses the political and economic impact on cross-Strait relations of common membership. The book begins with an introduction which analyzes the state of cross-Strait economic and political relations on the eve of dual accession to the WTO and briefly introduces the chapters which follow. The first chapter discusses the concessions made by both sides in their accession agreements and is followed by two chapters which describe the manner in which the Taiwan economy was reformed to achieve compliance as well as the specific, restrictive trade regime that was put into place to manage mainland trade. The next two chapters deal with the implications of that restrictive trade regime for the Taiwan economy in Asia and with the nature of the interactions between the two sides within the WTO. The final four chapters of the volume examine the impact of membership on four sectors of the economy: finance; agriculture; electronics and automobiles. There is a post-script which briefly covers developments since the chapters were completed.